Self-injurious behaviors without suicidal intent: need for mental health promotion - García García, Eddy Eugenio (2021)
This work is a consequence of the question that the authors face in a growing problem, which is gaining more and more followers; self-injurious or self-destructive behaviors without suicidal intention, this practice consisting of deliberately causing damage to one's own body, specifically through cuts, burns, pinches, scratches, abuse of drugs and other substances, including food, can have, depending on whether they are serious, various intentions, in which suicide is not related. These behaviors are the product of some anomalies in the perception, mainly of adolescents, in which the individual seeks to hide a feeling of discomfort, of emotional pain, which will alleviate for a moment that feeling that he may be feeling, but that being Repetitive can lead to great depression and probable suicide. Conditioning factors, risk factors, and some strategies that point to the need to promote mental health urgently, especially in young people, are revealed.